Tolerance Limits of Barley, Peas and Lettuce Towards Composts Rich in Phenolic Compounds and Lipid Substances. Issue 12 (4th July 2018) - Fersi, Mariem; Smaoui, Yosr; Mechichi, Tahar; Hachicha, Ridha
ABSTRACT: Lipid and phenol elimination impact from composts on Barley's development and phytotoxicity tolerance limits of other seeds were investigated. Thus, compost C1 was freed of its lipids and phenols and then reintroduced separately or together at different concentrations. Correlations between germination index (GI), phenol (Ph.I.) and fat (Ft.I.) toxicity indexes were examined. Results showed that lettuce seems to be the most affected by high concentrations of these compounds. Phytotoxicity was detected when concentrations were 5000 and 7500 ppm, respectively, for phenols and fats. Barley was the most tolerant, until 12500 ppm where a slight toxicity was detected with a GI of 65 and Ft.I. of 3. This became more important when the concentration reached 15000 with a GI of 38 and Ft.I. of 4. At 7500 ppm of phenols, barley and peas showed a limit of tolerance since the GI obtained was 49 and 62%, respectively.